The Role of Semantic Occasionalisms in V. S.Vysotsky’s Poetry - Shkrobova, Irina A. (Respectus Philologicus, 2003)
The distinctive feature of fiction is that it bears not only semantic but the so-called aesthetic information. A thoughtful reader along with what the author wants to say appreciates the way it is expressed. Therefore, the paper investigating the writer’s work focuses on the way the author uses the language. The paper explores several methods used to create semantic occasionalisms in V. S. Vysotsky’s poetry. The combinations in which lexemes change their meaning under the influence of a prop semantic co-occurrence element are analyzed, as well as modeling of occasional combinations.